Prefilled syringes: An innovation in parenteral packaging - Makwana, Sagar; Basu, Biswajit; Makasana, Yogita; Dharamsi, Abhay (International Journal of Pharmaceutical Investigation)
Parenteral administration of pharmaceutical products is one of the most popular methods used to produce quick onset of action and also 100% bioavailability. Main problem occurs with the parenteral drug delivery is lack of convenience, affordability, accuracy, sterility, safety etc. Such drawbacks with this delivery system makes it less preferable. Hence, all the disadvantages of these systems can be easily overcome by use of prefilled syringes. The objective of this review article is to provide information regarding prefilled syringes; it’s method of preparation, direction to use, advantages, its future scope, and development.
Keywords: Bioavailability; parenteral; prefilled syringes